Investigação do modelo de aprendizagem híbrido genético-baseado em instâncias - Nardin, Luciana de (Universidade Federal de São Carlos, 2003)
This research work investigates the contribution of genetic algorithms to instance based learning methods, particularly k-NN, IB1 and IB2. The main focus of the investigation is to optimize the performance of three algorithms by means of a genetic algorithm. A computational system that implements each method and its genetic variant is described. Results of experiments in some knowledge domains are presented and analised.
Keywords: Aprendizagem de máquina; Aprendizado baseado em instâncias; Algoritmos genéticos; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO